Syzygium aromaticum (clove buds) as a natural antibacterial agent: a promising alternative to combat multidrug-resistant bacteria - Tariq, Hira; Alhudhaibi, Abdulrahman Mohammed; Abdallah, Emad M. (Frontiers in Microbiology, 2025)
Antibiotic resistance is a critical threat to modern medicine, necessitating new strategies against multi-drug resistant bacteria (MDR). This narrative review evaluates the published evidence on Syzygium aromaticum (clove) and its principal phytochemicals, with particular focus on activity against MDR pathogens. We describe the chemical profile, notably eugenol, quercetin, kaempferol, β-caryophyllene, and α-humulene, and summarize reported in vitro activity and substantial biofilm inhibition (up to about 90%) against clinically relevant MDR bacteria such as Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae. Mechanistically, clove phytochemicals act through a hierarchical cascade in which membrane perturbation is the primary initiating event. Lipophilic constituents (notably eugenol) partition into and disorder the phospholipid bilayer, causing rapid loss of membrane potential, K+/ATP efflux and collapse of the proton-motile force (PMF). This primary membrane failure then enables secondary intracellular consequences, impaired electron transport and tricarboxylic acid cycle (TCA-cycle) enzyme activity, increased electron leakage with reactive oxygen species (ROS) generation, macromolecular damage (lipid peroxidation, protein oxidation, DNA strand injury), and functional inhibition of energy-dependent efflux, which together produce bactericidal outcomes and potentiate synergy with conventional antibiotics. Importantly, phytochemicals from clove frequently act synergistically with conventional antibiotics, lowering antibiotic MICs by approximately 4–128-fold and enhancing agents including colistin, imipenem, and amikacin. We evaluate formulation approaches (nano-emulsions, liposomes, solid-lipid nanoparticles) aimed at improving delivery and bioavailability, and we review limited preclinical and early clinical observations that suggest benefits in settings such as ventilator-associated pneumonia and MRSA wound healing. Critical translational gaps remain. Robust in vivo efficacy data, standardized pharmacokinetic and toxicology characterization, stability studies, and rigorous clinical trials are urgently needed. We conclude by proposing a focused research roadmap to validate and responsibly translate clove-derived candidates as adjuncts to existing antibiotic regimens.